Determinants of Customer Loyalty in Internet Service Providers: The Mediating Role of Customer Satisfaction in Batam - Zulhad Abdurrahim Usyel; Edy Yulianto Putra; Dessy Aliandrina (Dinasti Review, 2026)
The swift progression of digital technology has significantly increased public dependence on internet services, intensifying competition within the internet service provider (ISP) industry. In this context, identifying the key drivers of customer satisfaction and loyalty becomes critical, particularly in developing urban areas such as Batam City. This research seeks to analyze the influence of product quality, information quality, and experience quality on customer satisfaction, as well as their subsequent implications for customer loyalty. The theoretical foundation of this research is grounded in service quality theory, customer satisfaction theory, and customer loyalty literature within service marketing. A quantitative research approach was employed using a survey method, with data collected through online questionnaires from 322 ISP users in Batam City. The findings highlight the importance of product and experience quality in improving customer satisfaction, while information quality appears to play a limited role. Furthermore, customer satisfaction has a strong and significant effect on customer loyalty and serves as a mediating variable in the relationship between product quality and experience quality with customer loyalty. The study concludes that enhancing technical performance and customer experience is critical for fostering customer satisfaction and supporting sustained customer loyalty in the ISP industry.